PENGARUH BUDAYA KERJA, LINGKUNGAN KERJA, DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN (Studi Kasus Pada Tenaga Kerja di DKI Jakarta) - Jasmine Anindya Putri (2022)
This quantitative research aims to test and see "The Influence of Work Culture, Work Environment, and Compensation on Employee Job Satisfaction (Case Study on Workforce in DKI Jakarta)." Respondents in this study were 100 permanent employees who are domiciled in DKI Jakarta as the sample here. The analysis technique used in this study is the Coefficient of Determination Test, T Test (Partial) and F Test (Simultaneous) using Smart PLS 3.0 software. The test results obtained results (1) Work Culture has a significant effect on Work Satisfaction of workers in DKI Jakarta (2) Work Environment has a significant effect on Job Satisfaction of workers in DKI Jakarta, (3) Compensation has a significant effect on Work Satisfaction of workers in DKI Jakarta and (4) Work Culture, Work Environment and Compensation have a significant effect on Work Satisfaction of workers in DKI Jakarta.